Determinants of uncontrolled blood pressure among adult hypertensive patients on follow-up at Negelle and Adola General Hospital, Guji Zone, Southern Ethiopia: facility-based case control study - Azmach Habtegiorgis; Alo Edin; Kebebew Lemma; Takala Utura; Dereje Girma; Dawit Getachew; Teshome Bekele (BMC Public Health)
Abstract Background Uncontrolled blood pressure is a significant public health problem associated with a high rate of mortality and morbidity worldwide. In Ethiopia, 48% of hypertensive patients have Uncontrolled blood pressure. Therefore, this study aimed to identify the determinants of uncontrolled blood pressure among adult hypertensive patients on follow-up at the Negele and Adola General Hospitals in the Guji Zone, Oromia, Ethiopia. Methods A facility-based, unmatched case–control study was conducted in Negelle and Adola General Hospitals, Guji Zone, from January-01–30, 2023, on 384 samples. Study participants were selected consecutively as they came for treatment until the required sample size was obtained. The data were collected using an interview-administered structured questionnaire and medical chart review. The data were entered into Epi-data version 3.1 and exported to SPSS version 25 for analysis. Binary logistic regression analysis was used to model the association between the dependent and independent variables. The candidate variables with p < 0.25 in the bivariate analysis were entered into the multivariable logistic regression. An Adjusted Odds ratio (AOR) and 95% CI were used to measure the strength of the association. Finally, at p < 0.05, statistical significance was declared. Results A sample of 384 respondents (128 cases and 256 controls) were included, for a response rate of 100%. No adherence to medication (AOR = 2.01, 95% CI = 1.16–3.44), no adherence to smoking abstinence (AOR = 1.84, 95% CI = 1.05–3.22), no adherence to weight management (AOR = 2.02, 95% CI = 1.04–3.92), poor hypertension knowledge (AOR = 2.18, 95% CI = 1.26–3.76), use of traditional medicine (AOR = 9.13, 95% CI = 5.31–15.69), and overweight (AOR = 3.35, 95% CI = 1.79–6.26) were significantly associated with uncontrolled blood pressure. Conclusion This study revealed that no adherence to medication, smoking, weight management, poor hypertension knowledge, traditional medicine use, and being overweight were determinants of uncontrolled blood pressure. Since these are modifiable and preventable factors, there is a need to implement interventions that will enhance self-care practices in this population to improve treatment outcomes.